Specialized trauma outpatient clinic experience in child and adolescent psychiatry - (:unkn) unknown (KLINIK PSIKIYATRI DERGISI, 2019)
Objective: Traumas are the experiences which can lead to serious emotional, psychological, cognitive and behavioral problems for child and adolescent. Traumatic events are the insistent events like natural disasters such as earthquake, floods, childhood neglect and abuse, forced abduction, traffic accidents, the diagnosis of a life-threatening illness. In this study, it was aimed to share the findings obtained from a specialized trauma outpatiet clinic for patients who were referred to Kocaeli University Faculty of Medicine, Child and Adolescent Psychiatry outpatient unit, emergency and forensic outpatient clinic and child protection unit due to their traumatic experiences. Method: The follow-up and evaluation of 81 patients who were followed-up at the trauma outpatient clinic between July 2015 and January 2016 were retrospectively reviewed; sociodemographic data, gender, type of trauma and diagnostic distributions were analyzed. Results: 11 of the patients were male (13.5%) and 70 were female (86.5%) and the mean age was 13.13 +/- 2.85 years. It was observed that 65 patients (80.3%) had sexual abuse and 16 patients (19.7%) were admitted to clinic after traumatic experiences such as loss of limb, parental loss, vehicle accident. Exposure to sexual abuse was significantly higher in girls than in boys (x(2) =9.72; p<0.05). 10 patients (12.3%) were not diagnosed with any psychiatric disorder, 71 patients met the diagnostic criteria of posttraumatic stress disorder (PTSD). Of those diagnosed with post-traumatic stress disorder, 7 were male and 64 were female. PTSD was observed more frequently in girls (x(2) =6.78; p<0.01). Discussion: The risk of exposure to traumatic experiences of children and adolescents is increasing nowadays; in our study, it was aimed to emphasize the importance of a specialized polyclinic setting which is followed and treated for traumatized child and adolescent patients.
Keywords: Child; Adolescent; Sexual Abuse; Trauma Outpatient Clinic; POSTTRAUMATIC-STRESS; SYMPTOMS